Imaging Features of Rare Hepatic Tumors - Raghunandan Vikram; Achal Sarna; Nir Stanietzky (Thieme Medical and Scientific Publishers Pvt. Ltd., 2023)
Hepatic lesions are commonly encountered in radiology practice. Lesions with classic imaging findings such as hepatocellular carcinoma, cholangiocarcinoma, hemangiomas, focal nodular hyperplasia, and adenomas are well described in literature and easily diagnosed by most experienced radiologists. In the appropriate context, metastases, which are one of the most common lesions encountered by radiologists who practice in predominantly cancer care settings, are also easily diagnosed. However, one may encounter rarer neoplasms which may be challenging to diagnose and manage. Often, these lesions have overlapping imaging features with those of the common lesions mentioned above. Diagnosis of these rarer tumors would require not only interpreting the images in the context of patient's demographics and clinical presentation but also recognizing the unique imaging features of these tumors. The literature is sparse in describing the radiological appearances of these tumors. Diagnosis based solely on imaging criteria is not advised in these instances. Histological confirmation or other prudent follow-up strategies are necessary for confirmation of imaging findings and interpretation. In this article, we will describe known imaging features of a few rarer primary malignant and benign neoplasms in the liver.